Comportamento clínico e laboratorial de selante bioativo com partículas S-PRG em dentes com lesões iniciais de cárie - PENHA, Karla Janilee De Souza (2020)
The self-etching sealant with SPR-G particles can be effective in the prevention and control of caries, as they are a simple, conservative and practical strategy for the treatment of teeth in the initial stages of eruption. The purpose of Chapter I was to evaluate in vitro the alkalinizing potential, adhesive strength and microhardness in vivo, retention and quality of the remainder of the self-etching sealant with pre-reacted glass (S-PRG). Sealants were used; Conventional FS (Fluoroshield-Dentsply) and BS - self-etching with pre-reacted particles (S-PRG) (BeautiSealant -Shofu) for the performance of in vitro and in vivo tests. For the analysis of the alkalinizing profile, 10 FS and BS sealant discs were made, submerged in Ph 7 and 4 solutions, evaluated after 24h and 30 days. For shear (SBS), 6 cylinders were made with FS or BS on each of the 20 bovine enamel surfaces, totaling 120 samples. For the measurement of Knoop microhardness, 20 circular samples were made with FS and BS, and the reading was performed after 24h and 30 days. For the randomized clinical trial with a split-mouth model, 28 adolescents (10 to 14 years old) were selected, with two permanent 2nd molars erupting, ICDAS≤2. BS and FS sealants were applied and treatments were evaluated in baseline and after 1 month, adopting the retention and quality criteria of the remaining material (USPHS). ANOVA, Scheffe's post-hoc was used to evaluate pH and T test for SBS and microhardness, and x2 and Fisher for in vivo analyzes (p <0.05). BS in acidic medium promoted an increase in pH after 24h and 30 days, and the pH remained stable in alkaline medium (pH> 7), in both situations FS acidified the medium. A reduction in SBS (p = 0.009) and microhardness (p = 0.00) was observed after 24h and 30 days, with the FS showing higher values in vitro. Clinically, the retention rate was higher for FS when compared to BS (p = 0.02), but there was no difference in the quality of the remaining sealants studied. The ICDAS profile was initially 1 and 2 for the treated groups and after 1 month, both groups had a higher incidence of ICDAS 0 (healthy and fully sealed teeth) (p = 0.275). After 1 month, the BS sealant, in vitro, showed less retention and microhardness, but with a greater tendency to alkalinize the medium and in vivo obtained the same level of clinical performance as the conventional sealant. In Chapter II, the objective was to evaluate the retention and survival analysis of conventional and self-etching resinous sealants with S-PRG particles for the sealing of permanent molar fissures and fissures after 1 year of treatment. A randomized mouth-divided clinical trial was carried out, where 56 newly erupted permanent second molars (Eruption stage 2 and 3), with ICDAS from 0 to 2, were selected. They received treatments with: FS and BS at random. Retention, quality of remnant (USPHS) and ICDAS assessments were performed at baseline and after 1, 6 and 12 months. Wilcoxon tests, chi-square of independence, Kaplan-Meier and Mantel-Cox survival analysis were performed (α = 5%). The proportion of total retention was significantly higher for FS (57.1%) compared to BS (21.4%) (p = 0.022). There was no difference in the quality of the remaining sealant (USPSH) of the sealants after 1 year of treatment. There was an association of ICDAS and sealants after 6 (p = 0.025) and 12 months (p = 0.027). BS showed less retention than FS, however the quality of the remaining sealants over 12 months was similar between the materials, and after 6 and 12 months of treatment there was a predominance of ICDAS 0 for BS, while FS presented ICDAS 1. The The objective of Chapter III was to evaluate the retention, marginal impairment and quality of the remainder of conventional resin sealants and bioactive self- etching using microscopic analysis of the teeth treated in a randomized clinical trial. Fifty-six newly erupted 2nd molars of adolescents aged 11 to 14 years were randomized and sealed with FS and BS. Moldings were made and cast with epoxy resin after treatment 1, 6 months and 12 months, totaling 224 samples. Direct (clinical) and indirect (microscopic) assessments of retention, quality of remnant (USPHS) and marginal impairment were performed. The indirect data were submitted to the x2 test for the degree of retention, ordinal regression with Logit function with odds ratios for the quality of the remainder, and for the reliability between the clinical and microscopic evaluations, Fleiss-Kappa (α = 0, 05). It was clinically observed that BS (79.2%) obtained less total retention than FS (36.8%) only after 1 year (p = 0.005). There was no difference in the anatomical shape (p = 0.465) of the sealants, but the adaptation and marginal impairment was better for FS only after 1 year (p = 0.012). In 1 month, the chances of BS showing greater marginal impairment was 2.99 times greater than those of FS, and after 1 to there was only a 0.2931 times chance of repeating this pattern. The microscopic evaluation was 0.20 higher than the clinical one. It was possible to conclude that only after one year did the FS sealant show greater retention and marginal adaptation / compromise values, and the microscopic values were able to confer more accuracy than the clinical evaluation (tactile-visual).